2007
DOI: 10.1890/06-2079.1
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Mechanisms of Pollution Resistance in a Marine Invertebrate

Abstract: Abstract. Pollution is a common stress in the marine environment and one of today's most powerful agents of selection, yet we have little understanding of how anthropogenic toxicants influence mechanisms of adaptation in marine populations. Due to their life history strategies, marine invertebrates are unable to avoid stress and must adapt to variable environments. We examined the genetic basis of pollution resistance across multiple environments using the marine invertebrate, Styela plicata. Gametes were cros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 45 publications
0
39
0
Order By: Relevance
“…Previous studies have detected similar patterns, finding that environmental stress reduces additive genetic variance (Bubliy & Loeschcke, 2002; Galletly et al., 2007) and increases nonadditive genetic variance (Blows & Sokolowski, 1995; Jinks, Jean, & Pooni, 1973). However, other studies have found stress to have the opposite effect, or little effect at all (Hoffmann & Parsons, 1991; Pakkasmaa, Merila, & O'Hara, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have detected similar patterns, finding that environmental stress reduces additive genetic variance (Bubliy & Loeschcke, 2002; Galletly et al., 2007) and increases nonadditive genetic variance (Blows & Sokolowski, 1995; Jinks, Jean, & Pooni, 1973). However, other studies have found stress to have the opposite effect, or little effect at all (Hoffmann & Parsons, 1991; Pakkasmaa, Merila, & O'Hara, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…For many marine organisms, therefore, survival at this early stage of the life cycle will be a critical bottleneck in the persistence of future populations. Galeolaria 's free‐spawning nature also makes it ideal for exploring larval vulnerability to environmental stress using cross‐classified breeding designs, whereby the subdivision of ejaculates and egg clutches allows males to be mated with multiple females and vice versa (Galletly, Blows, & Marshall, 2007; Munday et al., 2013). Using such a design, we decomposed phenotypic variance in larval survival within and across thermal environments into its nonadditive genetic and maternal environmental components (partitioned from additive genetic effects; see Chirgwin, Monro, Sgro, & Marshall, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Styela plicata is a broadcast spawning, solitary ascidian and a simultaneous hermaphrodite (although self-sterile) (65). S. plicata is thought to be invasive to eastern Australia, is common on made-made structures (growing both in isolation and in clumps), and in vitro fertilization by strip-spawning techniques is straightforward (66). Adult S. plicata were collected and field manipulations conducted at Manly Boat Harbor (Brisbane, Australia; 27.467 E 153.183 S).…”
Section: Methodsmentioning
confidence: 99%
“…This procedure allowed the eggs to be retained inside the filter, whereas the sperm passed through into the beaker. Where eggs were required for fertilization experiments, we briefly soaked them in 0.5 M potassium chloride to kill any remaining sperm (66).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation